Hemp-lime bio-composites – properties and applications in architectural design - Gołębiewski, Michał (Видавництво Львівської політехніки, 2017)
This paper discusses physical properties and applications of hemp-lime bio-composites in architectural design. Hempcrete is a new, innovative construction material with significant ecological benefits, which gains popularity all over the world. Research on this topic is being conducted in many areas: material science, civil engineering, agriculture, ecology and architecture. The aim of this work was to review the worldwide publications and systemize the knowledge about the issue to provide information designated mainly for architects.
Keywords: hempcrete; hemp-lime composite; sustainable construction materials